Irvingia gabonensis seed fat as hard stock to formulate blends for trans free margarines. (March 2019) - Yamoneka, J.; Malumba, P.; Lognay, G.; Blecker, C.; Danthine, S.
Abstract: In order to formulate trans -free margarines, Irvingia gabonensis seed fat (IGF) was blended with a liquid oil which was either rapeseed oil (RO), groundnut oil (GNO), palm super olein (PSO) or Dacryodes edulis pulp oil (DPO). All the binary fat blends were evaluated in terms of melting behavior by Differential Scanning Calorimetry and p -NMR. Based on their melting behaviors by p -NMR, four blends (IGF/RO 30:70, IGF/GNO 30:70, IGF/GNO 20:80 and IGF/RO 20:80) were selected as having melting profiles closed to those of fat extracted from commercial margarines and literature data. Some physical properties of the selected fat blends such as solid fat content, hardness (by penetration) test, microstructure using an optical microscope and polymorphism using X-Ray Diffraction were evaluated. Those four trans -free fat blends showed similar hardness and solid fat content (SFC) than fats extracted from commercial bakery margarine, baking margarine and table margarine during storage experiments. All those four fat blends showed β' crystals as stable polymorphic form, which is desirable for margarines. Therefore, those four fat blends are suitable to formulate trans -free margarines with desirable textural properties. Highlights: Irvingia gabonensis seed fat is a natural lauric fat with a complete meting around 40 °C. When it is blended with liquid oils, the melting point of the blends decreased. Its blends with 80, 70% of Rapeseed oil or Groundnut oil presented melting and textural properties close to commercial margarine fats. These selected blends are trans free fatty acids with low atherogenic and thrombogenic indices.